The efficacy of 30% FENBENDAZOLE anthelmintic paste in cyathostominosis in horses - Corina Badea; Florin Ş. Hora; Sorin Morariu; Gheorghe Dărăbuş (Medicamentul Veterinar)
Horse cyathostominosis is a large intestine helminthosis caused by parasites belonging to the family Strongylidae, subfamily Cyathostominae. The cyathostomins (small strongyles) represent a challenge for the parasitologists and animal owners due to the different ontogenesis, the high number of parasite species and their ability to develop anthelmintic resistance. The faeces were examined by flotation (Willis) method and the infestation level was determined by McMaster method in day 0, 7 and 14 post treatments. The product Vanbendazol (30% fenbendazole) had a 97.7% efficacy in the treated horses from Şofronea, Arad County, using the Faecal egg count reduction test (FECRT). Also were performed Presidente and Borgsteede relations and the anthelmintic efficacy was 98.2% for the both relations.